New Evidence on Classroom Computers and Pupil Learning - Joshua D. Angrist; Victor Lavy (Institute for the Study of Labor (IZA), 2001)
The question of how technology affects learning has been at the center of recent debates over educational inputs. In 1994, the Israeli State Lottery sponsored the installation of computers in many elementary and middle schools. This program provides an opportunity to estimate the impact of computerization on both the instructional use of computers and pupil achievement. Results from a survey of Israeli school-teachers show that the influx of new computers increased teachers? use of computer-aided instruction (CAI) in the 4th grade, with a smaller effect on CAI in 8th grade. Although many of the estimates are imprecise, on balance, CAI does not appear to have had educational benefits that translated into higher test scores. OLS estimates show no evidence of a relationship between CAI and test scores, except for a negative effect on 8th grade Math scores in models with town effects. IV estimates for 4th graders show lower Math scores in the group that was awarded computers, with smaller (insignificant) negative effects on language scores.
Keywords: J24; H41; I28; 330; Education; schools; computer-aided instruction; program evaluation; Computergestütztes Lernen; Allgemeinbildende Schule; Bildungsniveau; Schätzung; Israel